Apology strategies in English used by Malay undergraduates / Noorhayati Baharudin - Noorhayati , Baharudin (2016)
This study aims to investigate the apology strategies in English used by 30 Malay undergraduates in Malaysia. It looks into the frequency, combination and sequential position of apology strategies used. The results reveal that the respondents employed different combinations of strategies to apologize. The use of apology strategies varied across six social situations. Most of the responses started with expression of apology (IFID) followed by other strategies. The most common combinations employed are expression of apology and explanation or account, expression of apology and repair and forbearance and expression of apology, acknowledgement of responsibility and minimizing the degree of offense. There is no significant difference in the way both gender apologized as they employed similar strategies in their oral responses. The respondents used two to three strategies the most to apologize. Finally, factors such as age, gender, social distance and severity of the offense play an important role in determining the strategies chosen to apologize.